The Role of Participatory Budgeting in Improving Performance in light of Covid 19 (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The current research aims to analyze the role of participatory budgeting in improving performance, especially during crises such as the Covid-19 crisis. The research used the descriptive analytical method to reach the results by distributing 100 questionnaires to a number of employees in Iraqi joint stock companies and at multiple administrative levels. The research came to several important conclusions, the most important of which is that the bottom-up approach to budgeting produces more achievable budgets than the top-down approach, which is imposed on the company by senior management with much less employee participation. Additionally, there is a better information flow from the lower levels of the organization to the upper management, which gives the upper management a better understanding of the issues the organization is facing. This is better for the behavioral spirit of the employees who are trying to put forth more effort to achieve what they anticipated in the budget. By promoting employee engagement in the resultant budget and performance review, the participatory budget may also help the business achieve its goals.